2014
DOI: 10.1186/1471-2164-15-221
|View full text |Cite
|
Sign up to set email alerts
|

From root to fruit: RNA-Seq analysis shows that arbuscular mycorrhizal symbiosis may affect tomato fruit metabolism

Abstract: BackgroundTomato (Solanum lycopersicum) establishes a beneficial symbiosis with arbuscular mycorrhizal (AM) fungi. The formation of the mycorrhizal association in the roots leads to plant-wide modulation of gene expression. To understand the systemic effect of the fungal symbiosis on the tomato fruit, we used RNA-Seq to perform global transcriptome profiling on Moneymaker tomato fruits at the turning ripening stage.ResultsFruits were collected at 55 days after flowering, from plants colonized with Funneliformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 141 publications
(138 citation statements)
references
References 105 publications
6
125
0
Order By: Relevance
“…5). In WT, PSY gene was similarly expressed in MYC and NM conditions, even though a trend towards down-regulation under MYC treatment was observed in a previous RNA-seq experiment using the Moneymaker cultivar (Zouari et al 2014). Lastly, no expression differences were detected between MYC and NM conditions in the mutant backgrounds.…”
Section: Expression Pattern Of Ripening Marker Genes In Gr and Hp-1 Mmentioning
confidence: 64%
See 4 more Smart Citations
“…5). In WT, PSY gene was similarly expressed in MYC and NM conditions, even though a trend towards down-regulation under MYC treatment was observed in a previous RNA-seq experiment using the Moneymaker cultivar (Zouari et al 2014). Lastly, no expression differences were detected between MYC and NM conditions in the mutant backgrounds.…”
Section: Expression Pattern Of Ripening Marker Genes In Gr and Hp-1 Mmentioning
confidence: 64%
“…By contrast, in the hp-1 mutant where there was enhanced pigment production and overall light sensitivity due to the mutation, the AM symbiosis acted as a positive regulator. The enhanced flower and fruit productivity under MYC conditions was probably favored by the synergy between the mutation itself (high light-sensibility in leaves, higher photosynthesis) and mycorrhization, which stimulates photosynthesis both in leaves (Wright et al 1998;Kaschuk et al 2009;Schweiger and Muller 2015) and in fruits, at least as predicted on the basis of transcriptomic analysis (Zouari et al 2014). ICP-OES analysis showed that while the fruits from the WT mycorrhizal plants possessed 30 % more phosphate than those from non-mycorrhizal plants, no differences were detected in the fruits produced by the mutant mycorrhizal plants.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations